KEPENARIAN SUWITRI DALAM TARI TOPENG DI SLARANG LOR, DUKUHWARU, KABUPATEN TEGAL - Fatkhudin Tri Nugroho (Institut Seni Indonesia Surakarta, 2015)
The research entitled The Artistry of Suwitri in Masked Dance in the Village of SlarangLor in the Dukuhwaru District of Tegal discusses the process of Suwitri’s artistry as a maskeddancer in Slarang Lor and Suwitri’s performance inTari Topeng Slarang Loror the Masked Danceof Slarang Lor. The method used in this research is qualitative interpretative. The techniques fordata collection include observation of recordings and direct observation, supported by a librarystudy and in-depth interviews. The theoretical foundation for uncovering the process of Suwitri’sartistry uses the theories of Habitus and Pierre Bourdie while the study of Suwitri’s performanceuses Janet Adshead’s dance analysis and the artistic demands for performing masked dance, whichinclude ngrungokena kendhang, gerakane kudu pas karo pakem, and ndelengna raineng topeng, or listening to the sound of the drum, making sure the movements follow the rules, andwatching the face of the mask. Suwitri is the only masked dance maestro who is able to perform 6different characters, as a result of her artistic background andthe process through which she learnedto dance to a level at which she has been affirmed as a maestro of Slarang Lor Masked Dance.Keywords: Artistry, Suwitri, Slarang Lor Masked Dance.